Surgical outcomes of reconstruction of soft tissue defects of the heel using various free flaps - Eun, Seokchan; Woo, Soo Jin (Acta Biomedica Atenei Parmensis, 2022)
Background: The goals of heel reconstruction are functional and aesthetic. Primarily due to the particular function of the heel in supporting the entire weight of the body while standing, these goals can be achieved by providing the heel with a durable and weight-bearing surface with adequate contour. Various methods such as skin graft, fasciocutaneous, and musculocutaneous local flaps have been reported for reconstructing this area. This retrospective study introduces different kinds of free flaps for heel reconstruction.Methods: Between July 2010 and September 2016, 13 patients underwent soft tissue reconstruction of the heel with anterolateral thigh flap, lateral arm flap, superficial circumflex iliac artery perforator flap, and temporalis muscle flap. Immediate and delayed postoperative results of the surgery were evaluated with satisfaction assessed subjectively among the patients.Results: There were 8 cases of anterolateral thigh flap (61.5%), 2 cases of lateral arm flap (15.3%), 2 cases of superficial circumflex iliac artery perforator flap (15.3%), and 1 case of temporalis muscle flap (7.6%). The mean duration of surgery was 261.69 (range, 114–442) minutes and the average length of absolute immobilization was 8.38 (range, 6–11) days. All flaps survived with 3 cases of minor revision due to partial necrosis, wound dehiscence, and bulky flap. There were no morbidities among donors. Satisfactory aesthetic and functional results were observed among all the patients.Conclusion: This article suggests that various free flaps can be considered as reliable options in heel reconstruction, resulting in acceptable functional and aesthetic outcomes.